Relevance of allosteric conformations and homocarnosine concentration on carnosinase activity - Peters, Verena; Kebbewar, Moustafa; Jansen, Erwin W.; Jakobs, Cornelis; Riedl, Eva; Köppel, Hannes; Frey, Dirk; Adelmann, Katja; Klingbeil, Kristina; Mack, Matthias; Hoffmann, Georg F.; Janssen, Bart; et al. (Amino acids, 2010)
Activity of carnosinase (CN1), the only dipeptidase with substrate specificity for carnosine or homocarnosine, varies greatly between individuals but increases clearly and significantly with age. Surprisingly, the lower CN1 activity in children is not reflected by differences in CN1 protein concentrations. CN1 is present in different allosteric conformations in children and adults since all sera obtained from children but not from adults were positive in ELISA and addition of DTT to the latter sera increased OD450 values. There was no quantitative difference in the amount of monomeric CN1 between children and adults. Further, CN1 activity was dose dependently inhibited by homocarnosine. Addition of 80 μM homocarnosine lowered Vmax for carnosine from 440 to 356 pmol/min/μg and increased Km from 175 to 210 μM. The estimated Ki for homocarnosine was higher (240 μM). Homocarnosine inhibits carnosine degradation and high homocarnosine concentrations in cerebrospinal fluid (CSF) may explain the lower carnosine degradation in CSF compared to serum. Because CN1 is implicated in the susceptibility for diabetic nephropathy (DN), our findings may have clinical implications for the treatment of diabetic patients with a high risk to develop DN. Homocarnosine treatment can be expected to reduce CN1 activity toward carnosine, resulting in higher carnosine levels.